Paracrine effects of mesenchymal stem cells induce senescence and differentiation of glioblastoma stem-like cells - Kološa, Katja; Motaln, Helena; Herold-Mende, Christel; Koršič, Marjan; Lah, Tamara T. (Cell transplantation, 2015)
Glioblastoma multiforme (GBM) displays high resistance to radiation and chemotherapy, due to the presence of a fraction of GBM stem-like cells (GSLCs), which are thus representing the target for GBM elimination. Since mesenchymal stem cells (MSCs) display high tumor tropism, we examined possible antitumor effects of the secreted factors from human MSCs on four GSLC lines (NCH421k, NCH644, NIB26, and NIB50).